Written code mixing of Bahasa Indonesia–English in a magazine - Zulfadli A Aziz; Diana Achmad; Maizura Maizura (Proceedings of AICS - Social Sciences, 2017)
The use of Bahasa Indonesia in the mass media such as magazines has been mostly influenced by English due to the use of the language as one of the main foreign language in Indonesia. Mass media have played crucial roles in promoting the foreign vocabulary by code mixing to make the writing become more prestigious and cool. The aim of this study is to find out the dominant type of code mixing used in the Aplaus magazine among three types of code mixing based on Musyken’s (2000) theory: insertion, alternation, and congruent lexicalization. The data of 47 code mixing were taken from Aplaus magazine in four editions from April to July 2016 on the Journey Section. In collecting the data, the researchers noted the occurrence of English code mixing in one of the sections in the magazine. Then, the data obtained were classified and tabulated. The results of this research show that not all of three types of code mixing by Musyken (2000) were applicable in the Aplaus magazine on the Journey section, there are found 36 instances or about 76.6 % for insertion, 11 instances or about 23.4 % for alternation, and no case of congruent lexicalization. So the dominant type of code mixing used in the Aplaus magazine was insertion.